The development of rainfall temporal pattern in Kuantan River Basin - Nurulain Fatin, Mahamed Zaidi (2016)
In the process of a design rainfall, information on rainfall duration rainfall temporal pattern analysis is very important especially in management of drainage design and rainfall. This study focuses on developing a temporal rainfall pattern for the Kuantan River Basin in Pahang. The existing data of rainfall temporal pattern design is not reliable because the climate change and the data of rainfall temporal pattern not renew since 2010. The rainfall temporal pattern is only divided by region in Malaysian Urban Storm Water Management Manual Second Edition (MSMA 2). This study provide rainfall distribution for the specific station area compared to the regional pattern provided in the MSMA 2. The rainfall temporal pattern were developed using Average Variability Method (AVM) which is sorted by rank 10 highest total rainfall data until the lowest one and Huff Time Distribution Method (HTDM) which is divided into four quartile. There are 10 number of station was selected. Data of every 5 minutes rainfall event for 16 years starting from 2000 to 2015 were gathered from Department of Irrigation and Drainage (DID) for purpose of this study. The temporal rainfall patterns developed are for 15 minutes, 30 minutes, 60 minutes, 180 minutes and 360 minutes duration. However, for HTDM only 60minutes, 180minutes and 360minutes rainfall duration are were selected. It is because the data of event need to divide into four quartile. The results show that the differences the rainfall temporal patterns of Kuantan River Basin developed in the study using method of Average Variability Method with the available value in MSMA 2 for the region of Pahang (Region 2). All station shows the different in the range 1%-1800% which is too high. It is because of specification area in developing the rainfall temporal pattern. The percentage of different increased since the duration of rainfall are increased. The rainfall temporal pattern develop in this study is specific on each station in Kuantan River Basin while the rainfall temporal pattern develop in the MSMA 2 is based on the region.